Attitudes to ageing and quality of life in young and old older adults: an international cross-sectional analysis. Issue 1 (12th December 2020) - Long, Sarah; Laidlaw, Kenneth; Lorimer, Angus; Ferreira, Nuno
Abstract : Purpose: Although quality of life and attitudes to ageing have been explored in the context of mental and physical health problems in older adults, the interplay between these variables has received little attention. The purpose of this study is to explore how attitudes to ageing relate to and predict quality of life in an international sample of older people those of age 57 to 79 (youngest-old) and those over 80 years old (oldest-old). Design/methodology/approach: A large international sample ( n = 4, 616) of participants recruited from 20 different countries completed a set of measures assessing several demographic variables, attitudes to ageing, older adult specific quality of life, general quality of life and depression. Findings: Correlational and regression analysis showed that more positive attitudes to ageing were associated with and predicted better quality of life in older adults beyond demographic and depression variables. Those in the oldest-old group had significantly more negative attitudes to ageing and a poorer quality of life. However, positive attitudes to ageing remained a significant predictor of better quality of life in both the youngest-old and oldest-old age groups. Originality/value: Attitudes to ageing play an important part in quality of life in older adults; however, the impact of these attitudes might be different according to age group. These results suggest that attitudes to ageing could be a possible clinical target in interventions aiming at improving quality of life in older adults.